Impact of economic disruptions and disease experiences on COVID-19 vaccination uptake in Asia: A study in Malaysia - Wagner, Abram L.; Rajamoorthy, Yogambigai; Taib, Niazlin M. (Narra J, 2021)
During the coronavirus disease 2019 (COVID-19) pandemic, individuals have had a variety of experiences with the disease and economic disruptions in Asia. We assessed how these experiences could impact COVID-19 vaccination intent and uptake in one of the Asian country, Malaysia. Two opt-in internet-based cross-sectional samples were collected: a March wave (26 March – 7 April 2021) and a June wave (22 June – 10 July 2021). Individuals were asked about their vaccination status, their employment status, and their experience with COVID-19 cases. The impact of economic disruptions and experiences with COVID-19 on COVID-19 vaccination was assessed through a multivariable, multinomial logistic regression model. Among 1,493 participants (735 in March and 758 in June wave), 26% were already vaccinated, 57% planned to vaccinate, and 17% had no plan to vaccinate. The number who had lost a job or earned less because of the pandemic was 30% in March and 36% in June. Across both waves, 5%-6% had a personal, very serious experience of COVID-19, 13%-16% knew of a family member or friend with a very serious experience of COVID-19, and 43%-61% knew of a very serious COVID-19 case through media. Notably, compared to those who worked the same amount throughout the pandemic, those who lost their job had lower odds of already being vaccinated (OR: 0.37; 95%CI: 0.23, 0.59), but similar odds of planning to become vaccinated. Personal, family/friend, and media experiences were also all related to increased odds of planning to vaccinated or being already vaccinated. The COVID-19 pandemic has led to large disruptions in people’s lives. People’s experiences during the pandemic impact their likelihood of being vaccinated or planning to vaccinate against COVID-19. Equitable allocation of COVID-19 vaccines will require outreach to groups with less stable employment and can leverage people’s experiences with disease during the pandemic.